2008
DOI: 10.1007/s00484-008-0182-3
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural network models of relationships between Alternaria spores and meteorological factors in Szczecin (Poland)

Abstract: Alternaria is an airborne fungal spore type known to trigger respiratory allergy symptoms in sensitive patients. Aiming to reduce the risk for allergic individuals, we constructed predictive models for the fungal spore circulation in Szczecin, Poland. Monthly forecasting models were developed for the airborne spore concentrations of Alternaria, which is one of the most abundant fungal taxa in the area. Aerobiological sampling was conducted over 2004--2007, using a Lanzoni trap. Simultaneously, the following me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 25 publications
(34 reference statements)
0
19
1
Order By: Relevance
“…However, the case might not be so for spore dispersal (Timmer et al 1998; Peternel et al 2004). The concentration of Alternaria spores in Poland was sometimes strongly correlated with temperature and low air humidity (Stepalska and Wolek 2005; Grinn-Gofron and Strzelczak 2008). Rodriguez-Rajo et al (2005) reported a negative correlation between length and severity of rainfall and concentration of spores.…”
Section: Discussionmentioning
confidence: 99%
“…However, the case might not be so for spore dispersal (Timmer et al 1998; Peternel et al 2004). The concentration of Alternaria spores in Poland was sometimes strongly correlated with temperature and low air humidity (Stepalska and Wolek 2005; Grinn-Gofron and Strzelczak 2008). Rodriguez-Rajo et al (2005) reported a negative correlation between length and severity of rainfall and concentration of spores.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum abundance of Alternaria spores was observed at the highest values of dew point temperature; however, it was not strong as mean air temperature. Sensitivity analysis of the artificial neural network showed dew point temperatures as the variable positively influencing the presence of Alternaria (Grinn-Gofroń and Strzelczak 2008a). The contrary results for dew point temperature were obtained by Troutt and Levetin (2001).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies were based on simple descriptive statistics, such as Pearson or Spearman’s correlation coefficients, or on multiple technique, such as the Duncan multiple range test and multiple regression model (Katial et al 1997; Angulo-Romero et al 1999; Mitakakis et al 2001; Troutt and Levetin 2001; Stennett and Beggs 2004). For the three types of spores ( Alternaria , Cladosporium and Ganoderma ), the predictive models were developed using advanced statistical methods like: artificial neural networks (ANN) and multivariate regression trees (MRT) (Grinn-Gofroń and Strzelczak 2008a, 2008b, 2009, 2011). All these studies put emphasis on the statistical analysis of the correlation between the level of concentration of particular fungal spore types and weather parameters, however do not examine the complex composition of spores and its dependence on meteorological factors.…”
Section: Introductionmentioning
confidence: 99%
“…Fungal spores are a biological component that can be found any time of the year in the atmosphere (Lacey, 1981;Burch and Levetin, 2002). Environmental variables, such as temperature and moisture, can influence growth and reproduction in fungi which makes airborne spore concentrations to fluctuate seasonally (Grinn-Gofrón and Strzelczak, 2008;Pakpour et al, 2015). However, it has also been observed that local climate, vegetation patterns, and management of landscape are governing parameters for the overall spore concentration, while the annual variations caused by weather, although not negligible, are of secondary importance (Skjøth et al, 2016).…”
mentioning
confidence: 99%